1979
DOI: 10.1136/pgmj.55.648.704
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of amitriptyline, mianserin, zimelidine and nomifensine in depressed patients

Abstract: SummaryThe cardiac effects of amitriptyline, mianserin, zimelidine and nomifensine on the systolic time intervals (STI) and on the high speed surface ECG have been studied in depressed patients. Amitriptyline increased pre-ejection period (PEP) index and the PEP/left ventricular ejection time (LVET) ratio of the STI (P <0.05 and P <0.02). It also increased heart rate significantly (< 0.02) and tended to prolong Q-T interval. Mianserin shortened QS2I (P <0.05) and LVET (P < 0-01) and prolonged PEP/LVET ratio (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
15
2

Year Published

1982
1982
1992
1992

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 28 publications
9
15
2
Order By: Relevance
“…No changes of clinical importance were found in ECG and blood pressure, which is in accordance with the low effect of the two drugs on the cardiovascular system [5].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…No changes of clinical importance were found in ECG and blood pressure, which is in accordance with the low effect of the two drugs on the cardiovascular system [5].…”
Section: Discussionsupporting
confidence: 80%
“…3]. Nomifensine inhibits the reup take of NA and DA in the synaptic gap, while the effect on 5-HT is weak [4], In clinical studies of both drugs concerned, minor anticholinergic, cardiovascular and sedative effects have been found [5]. Nomifensine shows a central stimulating effect [6], while zimeldine does not differ from placebo in this respect [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similar considerations must apply to the interpretation of our results for PEP/LVET ratio, which showed a tendency to increase during amitriptyline treatment: if pre-ejection period is unaffected by increase in heart rate, but LVET is shortened (Burgess et al, 1979a;Johnson et al, 1981), then the ratio PEP/LVET must inevitably increase as heart rate rises, independently of any drug effects on contractility. Cokkinos and coworkers (1976) showed that PEP/LVET was indeed increased when heart rate rose following atropine administration.…”
Section: Systolic Time Intervals (Sti)mentioning
confidence: 64%
“…Tricyclic antidepressants are widely believed to have depressant rather than stimulant effects on contractility, but there is little evidence that this is so when the drugs are used in therapeutic doses (Glassman & Bigger, 1981) and our results for amitriptyline and QS2 index are concordant with those of Burgess and co-workers (1979a). Most reports on studies with antidepressant drugs on STI have emphasised the effect of the drugs on PEP and PEP/LVET ratio (Burgess et al, 1978(Burgess et al, , 1979aBurckhardt et al, 1978;Taylor & Braithwaite, 1978) and some authors have entirely omitted the results of QS2 measurements (Thayssen et al, 1981).…”
Section: Systolic Time Intervals (Sti)mentioning
confidence: 99%
“…The only consistent effects of decrease in heart rate have been observed also with zimelidine and nomifensine (Burgess et al, 1979). The explanation for this phenomenon remains unknown.…”
Section: Discussionmentioning
confidence: 96%